Effects of different psychosocial interventions on death anxiety in patients: a network meta-analysis of randomized controlled trials - Lu, Jinhong; Yang, Youzhuan; Chen, Haiyun; Ma, Hongchao; Tan, Yulei (Frontiers in Psychology, 2024)
Objective: This research intended to assess and compare influence of psychosocial interventions in death anxiety in patients, providing evidence-based guidance for both patients and healthcare providers. Design: The present study exclusively gathered randomized controlled trials by comprehensively searching across multiple databases, comprising of PubMed, Embase, Cochrane Library, Web of Science, and Scopus. The methodological quality of the enrolled studies involved in the analysis was assessed using the Cochrane bias risk assessment tool, and data analysis was performed utilizing appropriate software. Results: This research, encompassing 15 randomized controlled trials with a cumulative sample size of 926 patients, spanned from the earliest possible date to December 2023. The findings of network meta-analysis unveiled that the Rational-Emotive Hospice Care Therapy significantly reduced death anxiety among patients (Sequentially Updated Cumulative Ranking Analysis: 100%).The ranking plot of the network suggested that the rational-emotive hospice care therapy exhibited superior efficacy as a psychological treatment for reducing the death anxiety of patients. Systematic Review Registration: https://www.crd.york.ac.uk/prospero, identifier: CRD42023484767Death anxiety (DA), while often considered an anxiety disorder, is more precisely defined as an ongoing and excessive concern about dying (1). It is essential, however, to differentiate between a pathological fear of death and a normal level of concern about mortality. According to terror management theory(2), the awareness of mortality is a universal condition that can evoke a spectrum of responses, from healthy emotional reactions to debilitating fear. Only when the anxiety becomes excessive, does it associate with clinical disorders, highlighting the nuanced nature of death anxiety (3). Additionally, the interchangeability of death fear and anxiety in literature often blurs